Analisis perilaku siswa yang kecanduan game online mobile legend - Irmayani Irmayani; Muhammad Anas (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
This study's objectives are 1) to determine the symptoms of students addicted to the Mobile Legends online game (MOBA). 2) to know the factors that influence students' addiction to the MOBA game. 3) to know the impact of addiction to the MOBA game on students. 4) Finding the role of self-management techniques to reduce MOBA game addiction. This research is qualitative with the type of case study research. The research subjects were two students who complained about the legendary mobile online game. The research instruments used were interviews, observation and documentation. The results showed 1) There are several symptoms of the students who are addicted to MOBA games; 2) Factors affecting students addicted to online games, namely: a) the existence of rewards, feedback on games b) reduce boredom c) eliminate stereotypes of loneliness d) social inability for addicted players e) low self-esteem and self-efficacy f) virtual environment. 3) The impact caused by online game addiction behaviour. 4) Efforts made by the teacher: a) Using an individual counselling approach, b) Conducting home visits.